The Undying Past - Sudermann, Hermann, 1857-1928; Marshall, Beatrice, 1861-1944 (Salt Lake City, UT : Project Gutenberg, 2010)
"The Undying Past" by Hermann Sudermann is a novel published in 1894. After years away in South America, Leo returns home to discover his closest childhood friend Ulrich has married a woman from Leo's shadowy past. This discovery threatens to unravel the passionate friendship between two men of vastly different temperaments. Set against the backdrop of German society, the story explores loyalty, secrets, and the inescapable weight of history as past and present collide with devastating consequences. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Undying_Past
Release date is 2010-10-28
Produced by Charles Bowen, from page scans provided by the Web Archive
Keywords: Germany -- Fiction; German fiction -- Translations into English; Sin -- Fiction